Multi-objective Optimization Design of Wet Friction Clutches - Jiang Kai; Li Hua; Chen Si; Li Shilei; Ren Rongzhi (Jixie chuandong, 2023)
The drag torque of the wet clutch affects the efficiency of the transmission, and the engagement torque of the clutch affects the reliability of the transmission. However, reducing the drag torque and increasing the engagement torque are generally contradictory. This study takes the wet friction clutch as the research object, and takes the inner diameter, outer diameter, radial groove depth, radial groove width and number of radial grooves, friction plate clearance of the wet clutch as the optimal design variables. The minimum drag torque and maximum engagement torque are the optimization objectives, the mathematical model of the optimization design is established, and the solution method of the optimization toolbox of Matlab is given. Taking a fracturing truck gearbox clutch as an example, the multi-objective optimization design is carried out. After optimization, the drag torque is reduced by 31.67%, and the engagement torque is increased by 33.51%. The results show that the optimization method used in this study is effective and can provide theoretical reference for the design of the friction plate structure and the optimization of clutch parameters.